2016
DOI: 10.1093/mnras/stw3374
|View full text |Cite
|
Sign up to set email alerts
|

Multiple populations along the asymptotic giant branch of the globular cluster M4

Abstract: Nearly all Galactic globular clusters host stars that display characteristic abundance anti-correlations, like the O-rich/Na-poor pattern typical of field halo stars, together with O-poor/Na-rich additional components. A recent spectroscopic investigation questioned the presence of O-poor/Na-rich stars amongst a sample of asymptotic giant branch stars in the cluster M 4, at variance with the spectroscopic detection of a O-poor/Na-rich component along both the cluster red giant branch and horizontal branch. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 43 publications
7
21
1
Order By: Relevance
“…The multiple populations in AGB stars in NGC 2808 was also confirmed by Marino et al (2017) who carried out a study combining spectroscopy and photometry. They also looked at NGC 6121 (M4) and found it hosts two main populations in agreement with the finding by Lardo et al (2017) that AGB stars show broadened distribution in close analogy with their RGB counterparts in the C UBI 1 −V diagram. We note, however, that their conclusion on NGC 6121 contradicts the result of MacLean et al (2016) who found that the AGB is populated by Na-poor and O-rich stars (from the analysis of 15 AGB and 106 RGB stars).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…The multiple populations in AGB stars in NGC 2808 was also confirmed by Marino et al (2017) who carried out a study combining spectroscopy and photometry. They also looked at NGC 6121 (M4) and found it hosts two main populations in agreement with the finding by Lardo et al (2017) that AGB stars show broadened distribution in close analogy with their RGB counterparts in the C UBI 1 −V diagram. We note, however, that their conclusion on NGC 6121 contradicts the result of MacLean et al (2016) who found that the AGB is populated by Na-poor and O-rich stars (from the analysis of 15 AGB and 106 RGB stars).…”
Section: Introductionsupporting
confidence: 78%
“…Moreover, from the [O/Fe]−[Na/Fe] distribution of the AGB stars studied by Marino et al (2017) we can infer that the Na-rich/O-poor stars account for 47%, which is close to our 2P AGB fraction of 53%. The photometric studies of Marino et al (2017) and Lardo et al (2017) also support the claim that NGC 6121 hosts multiple populations on AGB. Thus we believe that this cluster should have more than one stellar population along its AGB.…”
Section: Fractions Of 1p and 2p Starssupporting
confidence: 62%
See 1 more Smart Citation
“…There are at least a few photometric systems currently being used in the study of the MPs in GCs, but, very Lee unfortunately, the definition of MPs in GCs from various photometric studies can differ one from the other (see, e.g., Lardo et al 2011Lardo et al , 2017Lee et al 2009a,b;Lee 2017Lee , 2018Milone et al 2012Milone et al , 2017. The MPs study from broadband photometry tends to rely on the photometric measurements of absorption strengths of some very strong molecular bands, including OH, NH, CN, and CH.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, for the two GCs that have been studied more than once so far, conflicting evidence has been reported. In the case of M4 photometric inferences of population proportions (Lardo et al 2017) disagree with the spectroscopic results (MacLean et al 2016). The conflicting spectroscopic evidence for the other case, NGC 6752 (Campbell et al 2013;Lapenna et al 2016) is the topic of the current study.…”
Section: Introductionmentioning
confidence: 73%